Comparatıve Examınatıon of Romantıc Jeaolusy and Aggressıon Levels of Adult Indıvıduals wıth and wıthout Chıldhood Trauma - Onur Okan Demirci, Kahraman Güler, Gülesin Köşşekoğlu (Pakistan Journal of Medical & Health Sciences, 2022)
Childhood traumas are defined as the negative effects of sexual, emotional, physical abuse, emotional and physical neglect on the psychology and development of the individual under the age of 18. Romantic jealousy is defined as the individual's suspicion between his partner and a real or unusual person or as the individual's reaction to a threat to the romantic relationship. Aggression is defined as a harmful behavior. While the concept of aggression, in which the behavior is at the forefront, is expressed as an attitude that harms other people, in the definitions where the intention is at the forefront, it is defined as the attitudes and actions taken with the aim of hurting. In this study, it is aimed to comparatively examine the romantic jealousy and aggression levels of adult individuals with and without childhood traumas. This study was prepared in accordance with the correlational survey model. The sample selection of the study was made using simple-random sample selection type. The sample group of the study consists of 400 adult individuals in Istanbul. Participants were selected simple-randomly. The data collection process of the research took place in 2021. According to the findings obtained from the research, individuals with childhood trauma score higher in physical, emotional, cognitive, speaking, reprimand, dependency, indefference, positive effects, negative effects, sense of inadequacy, fear of loss, disruptive, assertiveness and passiveness sub-dimensions compared to individuals without childhood trauma. This situation reveals that individuals with childhood trauma have higher levels of romantic jealousy and aggression.